2022
DOI: 10.58968/fwm.v2i1.164
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Literature on Sharia Credit Card

Abstract: This study was carried out to examine the Islamic credit card within the context of Islamic economics in terms of scientific research produced in response to the introduction of Islamic credit cards. Descriptive bibliometric statistical analysis and sentiment analysis are applied to secondary data in the form of 134 papers published over the last nine years and then processed with VOSViewer and SentiStrength. The results demonstrated that bibliometric mapping is divided into two clusters, with cluster 1 contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…This method allows the research to categorize the tweets in this study based on the sentiment contained within their text, enabling an analysis of public views and attitudes toward green finance in the context of social media. Other studies using sentiment analysis can be found at Mu'adzah (2022), Maulida et al, (2022), Rusydiana (2022), Rahayu (2022), Maulida & Rusydiana (2023), Zaidan et al, (2022), andNuraini (2022).…”
Section: Methodsmentioning
confidence: 99%
“…This method allows the research to categorize the tweets in this study based on the sentiment contained within their text, enabling an analysis of public views and attitudes toward green finance in the context of social media. Other studies using sentiment analysis can be found at Mu'adzah (2022), Maulida et al, (2022), Rusydiana (2022), Rahayu (2022), Maulida & Rusydiana (2023), Zaidan et al, (2022), andNuraini (2022).…”
Section: Methodsmentioning
confidence: 99%